Tau positron emission tomographic imaging in aging and early Alzheimer disease. Issue 1 (15th December 2015) - Johnson, Keith A.; Schultz, Aaron; Betensky, Rebecca A.; Becker, J. Alex; Sepulcre, Jorge; Rentz, Dorene; Mormino, Elizabeth; Chhatwal, Jasmeer; Amariglio, Rebecca; Papp, Kate; Marshall, Gad; Albers, Mark; et al.
Abstract : Objective: Detection of focal brain tau deposition during life could greatly facilitate accurate diagnosis of Alzheimer disease (AD), staging and monitoring of disease progression, and development of disease‐modifying therapies. Methods: We acquired tau positron emission tomography (PET) using 18 F T807 (AV1451), and amyloid‐β PET using 11 C Pittsburgh compound B (PiB) in older clinically normal individuals, and symptomatic patients with mild cognitive impairment or mild AD dementia. Results: We found abnormally high cortical 18 F T807 binding in patients with mild cognitive impairment and AD dementia compared to clinically normal controls. Consistent with the neuropathology literature, the presence of elevated neocortical 18 F T807 binding particularly in the inferior temporal gyrus was associated with clinical impairment. The association of cognitive impairment was stronger with inferior temporal 18 F T807 than with mean cortical 11 C PIB. Regional 18 F T807 was correlated with mean cortical 11 C PiB among both impaired and control subjects. Interpretation: These findings suggest that 18 F T807 PET could have value as a biomarker that reflects both the progression of AD tauopathy and the emergence of clinical impairment. ANN NEUROL 2016;79:110–119